Submesoscale Ageostrophic Processes in the Kuroshio and Their Impact on Phytoplankton Community Distribution - Yuxuan Wang; Zheyue Shen; Jinjun Rao; Shuwen Zhang (Journal of Marine Science and Engineering)
This study focuses on typical regions of strong ageostrophic processes in the Kuroshio using high-resolution remote sensing satellite reanalysis data and Argo float data. By analyzing the relationship between the Rossby number and chlorophyll concentration from June to August in the summer of 2020, the spatial characteristics of ageostrophic processes and their impact on the phytoplankton community distribution are explored. The results indicate that ageostrophic processes, driven by coastal topography, are stably generated in the regions of the Bashi Channel, northeastern Taiwan waters, southwestern Kyushu Island, and southern Shikoku Island. Furthermore, the intensity of these ageostrophic processes shows an overall positive correlation with chlorophyll concentration. The local mixing and subfront circulations induced by ageostrophic processes pump deep nutrients into the euphotic zone, supporting the growth and reproduction of phytoplankton, which leads to the formation of significant chlorophyll hotspots in regions controlled by ageostrophic processes.